Where and when to hunt? Decomposing predation success of an ambush carnivore. Issue 12 (6th October 2020) - Smith, Justine A.; Donadio, Emiliano; Bidder, Owen R.; Pauli, Jonathan N.; Sheriff, Michael J.; Perrig, Paula L.; Middleton, Arthur D.
Abstract: Predator–prey games emerge when predators and prey dynamically respond to the behavior of one another, driving the outcomes of predator–prey interactions. Predation success is a function of the combined probabilities of encountering and capturing prey, which are influenced by both prey behavior and environmental features. While the relative importance of encounter and capture probabilities have been evaluated in a spatial framework, temporal variation in prey behavior and intrinsic catchability are likely to also affect the distribution of predation events. Using a single‐predator‐single‐prey (puma‐vicuña) system, we evaluated which factors predict predation events across both temporal and spatial dimensions of the components of predation by testing the prey‐abundance hypothesis (predators select for high encounter probability) and the prey‐catchability hypothesis (predators select for high relative capture probability) in time and space. We found that for both temporal and spatial analyses, neither the prey‐abundance hypothesis nor the prey‐catchability hypothesis alone predicted kill frequency or distribution; puma kill frequency was static throughout the diel cycle and pumas consistently selected a single habitat type when hunting, despite temporal and spatial variation in encounter rates and intrinsic catchability. Our integrated spatiotemporal analysis revealed that an interaction between time of day and habitat influences kill probability, suggesting that trade‐offs in the temporal and spatial components of predation drive the probability of predation events. These findings reinforce the importance of examining both the temporal and spatial patterns of the components of predation, rather than unidimensional measures of predator or prey behavior, to comprehensively describe the feedbacks between predator and prey in the predator–prey game.